Impact of switching from zidovudine/lamivudine to tenofovir/emtricitabine on lipoatrophy: the RECOMB study1. Issue 6 (9th January 2013) - Ribera, E; Larrousse, M; Curran, A; Negredo, E; Clotet, B; Estrada, V; Sanz, J; Berenguer, J; Rubio, R; Pulido, F; Ferrer, P; Alvarez, ML; et al.
<x xml:space="preserve">Abstract</x> Objectives Lipoatrophy is a long‐term adverse effect of some antiretrovirals that affects quality of life, compromises adherence and may limit the clinical impact of HIV treatments. This paper explores the effect of tenofovir/emtricitabine (TDF/FTC) on the amount of limb fat in patients with virological suppression. Methods A randomized, prospective clinical trial was performed to compare continuation on a zidovudine/lamivudine (ZDV/3TC)‐based regimen with switching to a TDF/FTC‐based regimen in terms of the effect on limb fat mass as assessed by DEXA over a 72‐week period. Results Eighty patients were included (39 in the TDF/FTC arm and 41 in the ZDV/3TC arm) and 73 completed the study (37 and 36, respectively). In the switch arm, limb fat increased by a median of 540 g from baseline (P = 0.022), while in the ZDV/3TC arm it decreased by a median of 379 g (P = 0.112; p between groups = 0.007). Subjects with baseline limb fat ≤ 7200 g, previous time on ZDV > 5 years or a body mass index > 25 kg/m2 experienced higher limb fat gains than other subjects, and these differences were statistically significant. Haemoglobin increased by a median of 1.0 g/dL in the TDF/FTC arm (P < 0.001) and remained unchanged in the ZDV/3TC arm (p between groups = 0.0002). There were no significant differences between groups in other secondary endpoints (body weight, total body and trunk fat content, total body bone mineral density, laboratory parameters, CD4 cell count and viral load). Conclusions Switching from a ZDV/3TC‐based to a TDF/FTC‐based regimen led to a statistically significant improvement in limb fat, in contrast to the progressive loss of limb fat in subjects continuing ZDV/3TC.